Physical frailty, cognitive and functional status in institutionalized older adults (Research, Society and Development, 2022)
Objective: To investigate the prevalence of frailty and its association with cognitive state and functional capacity in Brazilians institutionalized older adults. Methods: Cross-sectional study, conducted with institutionalized older adults from two Brazilian cities. Cognitive status, functional capacity and frailty were evaluated through the Mini-Mental State Examination (MMSE), KATZ index, and frailty phenotype, respectively, besides anthropometry and physical activity. Results: This study included 73 older adults with a mean age of 78.6 ±10.44 years. 63% were female, 47.9% were the very old (> 80 years) and 32.1% were underweight. The prevalence of frailty was 57.5%. It was observed that the older adults with frailty mostly had functional dependence (68.3%; p